(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2024)
The current research employed a traditional asset-based approach to evaluate the risk-management-capacity of the disaster-prone coastal communities in Bangladesh. A comprehensive survey that includes human perception through household Interviews, Key Informant Interviews (KII), and Focus Group Discussions (FGD) was conducted within Patharghata Upazila, a coastal sub-district in Bangladesh. Through qualitative analysis of the survey dat a, a wide spectrum of natural, built, and social assets, utilized by the locals in their daily lives and influencing their risk management capacity in the events of disasters, was elucidated. This underscores the potential for risk mitigation within vulnerable coastal communities of Bangladesh by maximizing the utilization of available resources. Additionally, the research conducted an ordinal regression analysis, the outcome of which revealed the relative influence of the various aspects of coastal residents’ living-standard on their risk managing capacity. The particular finding, household’s content with their access to basic necessities of life perceiving themselves as adequately prepared for potential disasters, underscores a positive correlation between households’ wellbeing and their strength against disasters. The implications of these finding extend to the policymakers of Bangladesh, highlighting the need for investments in developing the living status of the coastal communities for fostering disaster resilience within the coastal region of the country. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(1), 2024, P 141-154